JAMINAN KUALITAS PENERAP AN E-LEARNING - Prasojo, Latip Diat (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Quality assurance is all important systematic plan and action to provide trust applied to gratify certain requirement from quality. Quality assurance of e-learning is very importance in activity learning process teach Quality assurance of e-learning for study activity covers: need analysis, instructional planning, and evaluation. Quality assurance of e-learning has clauses as follows do adjustment of" the curriculum and curriculum character is competency based curriculum. Besides, teacher must do various way of teaching to reach iriterest ba.1·e which wish to be reached and provides study material kept in computer and can be accessed easily either by teacher and also student. Teacher must do assessment by exploiting existing technology (Online Assessment Syttem).